Performing freedom: Massive protest in the Catalan sovereignty process: From smiling to resisting. Issue 1 (1st July 2019) - Bartumeus, Sara; Vendrell, Ester
AbstractPolitical activism, performativity and social empowerment in contemporary public space are examined with a multi-disciplinary approach to analyse the mass choreographies organized in the sovereignty process of Catalonia. Through the lenses of the performing, visual and environmental arts (dance and architecture), this research looks at the interplay between public space and performance in collective protests, and its roles in shaping the collective experience and in the construction of the commoning.The study focuses on the largest peaceful marches ever organized in contemporary Europe, annually from 2012 to 2017 on September 11 (Catalonia National Day), by Catalan cultural and political activist associations (ANC and Òmniun Cultural) as massive collective actions in support of an independent republic state for Catalonia.The research aims to identify the unique elements of these long-time planned choreographies, and the repeated and embodied ones that are constructing a social identity influential in current semi-improvised protests.The choreography, iconography and impact of the protests are examined at different scales, from the emotional human experience and its local dissemination in social media, to the impressive visual experience of the aerial images at the city and the geographic scale, designed to be broadcasted live by global media. The study's goal is highlighting the design-thinking involved in these massive, peaceful and artistic expressions of emancipatory will, and its role and impact in the collective empowerment, the internal cohesion and the internationalization of the conflict in search of global empathy.